Cognitive analysis of the (Bingol Anti Terror Police Department) BATPD Buddy Program - Eren, Murat Erkan; Gulen, Engin (Journal of Human Sciences, 2015)
Buddy programs help newcomers to smooth transition. The programs also try to increase the performance of the new personnel, give them a moral support and provide a proper atmosphere. This study aims to figure out the deficiencies of the buddy program implemented in Bingol Anti-Terror Police Department (BATPD) and try to develop effective solutions for the program’s shortages. Thus, the newcomers are able to adapt to the organization in the fastest way without losing time and energy. In this study, the researcher applied observations and interviews to measure the effectiveness of the program. The participants were selected all of the newcomers who joined the organization in 2012. Data collection process took almost 12 months. According to results of the research, insufficient physical conditions of the unit, multitasking character of the personnel, and incompetent buddies are three reasons that hinder the program from being more successful. Training programs for buddies, focusing on one task at the one time, and more comfortable designed atmosphere in the organization are potential solutions for a better program.